The chronological change in transvaginal ultrasound images of a hemorrhagic ovarian cyst observed during infertility treatment: A case report and literature review. Issue 7 (9th July 2021) - Fujii, Yu; Wakimoto, Yu; Omote, Maya; Sugiyama, Yukiko; Ukita, Yuji; Kato, Toru; Fukui, Atushi; Shibahara, Hiroaki
Key Clinical Message: Insights gained from chronological ultrasonogram images in the current case report will provide useful information for diagnosing and conservatively treating HOC. This could help avoid unnecessary laparotomy. Abstract : Insights gained from chronological ultrasonogram images in the current case report will provide useful information for diagnosing and conservatively treating HOC. This could help avoid unnecessary laparotomy.